Open innovation in practice: diffusion of knowledge and use in Swedish bio-pharmaceutical firms. (1st January 2014) - Remneland-Wikhamn, Björn; Wikhamn, Wajda
The concept of open innovation has successfully diffused among academicians and policy makers, framing innovation work in the post-bureaucratic era. Much of its initial theorising is built on single case studies of early adopters, but there is still a lack of quantitative studies in specific industries and geographical contingencies. In this paper, we report the results of a survey on open innovation ( N = 114 firms), targeting the Swedish bio-pharmaceutical industry. The purpose is to shed light on how widespread the knowledge and practical utilisation of open innovation activities actually are in a particular industry. We find that very few respondents were aware of the open innovation concept, and also that open innovation related activities are, to a large extent, integrated within the ordinary innovation practices. At the same time, the application of open innovation activities relates to whether the firm has an innovation strategy, an own R&D department and has successfully launched innovations.